Cobalt/graphene oxide nanocomposites: Electro-synthesis, structural, magnetic, and electrical properties. Issue 9 (1st May 2022) - Iranshahi, Saeedeh; Mosivand, Saba
Abstract: In this research, different samples of cobalt/graphene oxide nanocomposites were successfully synthesized electrochemically by applying different voltages. Their structure, magnetization and electrical properties were studied using X-ray diffractometer (XRD), field emission scanning electron microscope (FESEM), atomic force microscope (AFM), fourier transformation infrared (FT-IR), vibrating sample magnetometer (VSM), two point probe electrical conductivity meter, galvanostat/potentiostat, and universal testing machine. The results of structural characterization confirmed the formation of cobalt/graphene oxide nanocomposites. The FESEM images showed the porous flower-like structure of particles deposited on the graphene oxide sheets. The AFM images clearly showed the surface roughness and the dispersion of nanoparticles on graphene oxide sheets. Room-temperature magnetization values range from 18 emu g −1 to 167 emu g −1, depending on the applied voltage. In order to study the electrical properties of the nanocomposites, the volumetric resistivity and volumetric conductivity under different pressures and the current-voltage characteristic curves were measured. Based on the results, the nanocomposites synthesized by applying 8 V and 23 V show ohmic behavior and have the highest volumetric conductivity. The volumetric conductivity increases with increasing the pressure. The nanocomposite prepared by applying 23 V presents good structural, magnetic, and electrical properties. Graphical abstract: Image 1